Association between physical activity and leisure-time sedentary behavior among 140, 808 adolescents aged 12 to 15 from 47 low- and middle-income countries. (October 2021) - Vancampfort, D.; Firth, J.; Smith, L.; Stubbs, B.; Rosenbaum, S.; Hallgren, M.; Van Damme, T.; Koyanagi, A.
Abstract: Objectives: Data from high-income countries (HICs) indicate that sedentary behavior is negatively associated with moderate-to-vigorous physical activity (MVPA) in young people. We examined associations between leisure-time sedentary behavior (LTSB) and MVPA in adolescents from 47 low- and middle-income countries (LMICs). Study design: Cross-sectional study. Methods: Data from the Global school-based Student Health Survey were analyzed in 140, 808 adolescents (13.8 ± 1.0 years; 49% girls). Time spent in LTSB was a composite variable assessing time spent sitting and playing computer games, watching TV, talking with friends during a typical day. The PACE + Adolescent Physical Activity Measure assessed MVPA levels. The association between ≥3 h/day of LTSB and adequate physical activity levels (every day last week 60 min MVPA) was explored with multivariable logistic regression analyses. Results: The prevalence of ≥3 h/day of LTSB and 60 min of MVPA/day last week were 26.3% (girls 26.2%; boys 26.5%) and 15.3% (girls 12.1%; boys 18.4%), respectively. LTSB of ≥3 h/day versus <3 h/day was associated with a 35% increased odds for adequate levels of MVPA in boys [OR = 1.35 (95%CI = 1.23–1.48)] and 22% in girls [1.22 (95%CI = 1.10–1.36)]. Conclusions: Our data indicate that being physically active 60 min per day every day and at moderate-to-vigorous intensity and being sedentary ≥3 h/day during leisure-time might co-exist in adolescents in some LMICs.